Ma'had Aly-Based Arabic Curriculum Management At As Sunnah Islamic College, North Sumatra - Iqbal, Muhammad; Santoso, Didik; Mesiono, Mesiono (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to provide an overview of Ma'had Aly-based Arabic Curriculum Management at As Sunnah Islamic College, Deli Serdang-North Sumatra. With a descriptive qualitative research method, it describes in depth the management of the Arabic language curriculum based on dormitories. As well as collecting data used by in-depth interviews, observation and documentation. These findings reveal that Ma'had Aly-Based Arabic Curriculum Management in all study programs with three management functions namely; 1) The planning of the ma'had aly-based Arabic curriculum is based on the Vision, Mission and Objectives of the tertiary institution, the institutional/Ma'had Aly/Syariah content curriculum, lecture schedules and activity schedules in the dormitories, competent educators, syllabus and lecturer lesson plan, Providing free books and providing adequate infrastructure. 2) The implementation of the ma'had aly-based Arabic curriculum contains Arabic language courses, placement of competent teachers, supporting activities in the dormitory such as daily, weekly, monthly and yearly activities, language habits and obligations in the campus and dormitory environment, Punishment using other than Arabic. 3) Evaluation of the ma'had aly-based Arabic curriculum is carried out by assessing the subjects during the MID and UAS exams, cumulative assessments, Toalf tests, and involving Internal Evaluators and External Evaluators.